Systematic Review of Outcome After Ischemic Stroke Due to Anterior Circulation Occlusion Treated With Intravenous, Intra-Arterial, or Combined Intravenous+Intra-Arterial Thrombolysis - Mullen, Michael T.; Pisapia, Jared M.; Tilwa, Shiv; Messé, Steven R.; Stein, Sherman C. (Stroke (1970), 2012)
The optimal approach to recanalization in acute ischemic stroke is unknown. We performed a literature review and meta-analysis comparing the relative efficacy of 6 reperfusion strategies: (1) 0.9 mg/kg intravenous tissue-type plasminogen activator; (2) intra-arterial chemical thrombolysis; (3) intra-arterial mechanical thrombolysis; (4) intra-arterial combined chemical/mechanical thrombolysis; (5) 0.6 mg/kg intravenous tissue-type plasminogen activator and intra-arterial thrombolysis; and (6) 0.9 mg/kg intravenous tissue-type plasminogen activator and intra-arterial thrombolysis. A literature search in Medline, Embase, and the Cochrane database identified case series, observational studies, and treatment arms of randomized trials of anterior circulation arterial occlusion treated with thrombolytic therapy. Included studies had ≥10 subjects, mean time to treatment <6 hours, and treatment specific reporting of disability, death, and intracerebral hemorrhage. Multivariable metaregression evaluated the effects of treatment group on outcome at the same time as accounting for differences in baseline covariates. A total of 2986 abstracts were identified from which 54 studies (5019 subjects) were included. There were significant differences across groups in age (P=0.0008), baseline National Institutes of Health Stroke Scale (P=0.0002), and time to treatment initiation (P<0.0001). There were also differences in mean modified Rankin Scale (P<0.0001), mortality (P=0.0024), and symptomatic intracerebral hemorrhage (P=0.0305). Differences in modified Rankin Scale were not significant in the metaregression and likely attributable to differences in baseline covariates between studies. This study found no evidence that one reperfusion strategy is superior with respect to efficacy or safety, supporting clinical equipoise between reperfusion strategies. Intravenous tissue-type plasminogen activator remains the standard of care for acute ischemic stroke. Randomized clinical trials are necessary to determine the efficacy of alternative reperfusion strategies. Participation in such trials is strongly recommended.